Modification of Deposited, Size-Selected MoS2 Nanoclusters by Sulphur Addition: An Aberration-Corrected STEM Study - Richard Palmer (Inorganics, 2017)
Molybdenum disulphide (MoS2) is an earth-abundant material which has several industrial applications and is considered a candidate for platinum replacement in electrochemistry. Size-selected MoS2 nanoclusters were synthesised in the gas phase using a magnetron sputtering, gas condensation cluster beam source with a lateral time-of-flight mass selector. Most of the deposited MoS2 nanoclusters, analysed by an aberration-corrected scanning transmission electron microscope (STEM) in high-angle annular dark field (HAADF) mode, showed poorly ordered layer structures with an average diameter of 5.5 nm. By annealing and the addition of sulphur to the clusters (by sublimation) in the cluster source, the clusters were transformed into larger, crystalline structures. Annealing alone did not lead to crystallization, only to a cluster size increase by decomposition and coalescence of the primary clusters. Sulphur addition alone led to a partially crystalline structure without a significant change in the size. Thus, both annealing and sulphur addition processes were needed to obtain highly crystalline MoS2 nanoclusters.